Setyawati, Ariesta BISNIS ONLINE DALAM PERSPEKTIF ISLAM - Setyawati, Ariesta; Nurislamiah, Siti; Hasim, Hasim; Rosbandi, Rosbandi (ISLAMIKA, 2024)
One of the mu'amalah phenomena in the economic field is buying and selling transactions using electronic media. Technological developments have spurred changes in individual habits, including carrying out buying and selling transactions. Previously, what was meant by buying and selling transactions had to be carried out face to face, where there was a direct transfer of goods from the seller to the buyer, that is, the buyer had to meet the seller in the real market. Currently, we have moved to an era where transactions are no longer carried out face-to-face, but rather via online media. From a fiqh point of view, online buying and selling is permitted in Islam in accordance with the rules of fiqh "Al-ashl fi mu'amalah al-ibahah, illaidza ma dalla al-dalil ala khilafihi, as long as in the process there are no elements that are contrary to Islam such as fraud, unclear and usury.